Homens invisíveis: identidades de homens atendidos pelas políticas sociais de atenção às famílias em situação de vulnerabilidade social - Souza, Paulo Fernando Pereira de (2009)
This dissertation aimed at understanding the identity of men benefited from social policies destined to the families in situation of social vulnerability. This study, of qualitative base, used the resource of the history of life and focused on subjects benefited from the Programa Ação Família (Family Action Program) of the Municipal City Hall of São Paulo, in the period from 2005 to 2008, and chose to deepen in the history of life of one of the subjects, which presented emblematic possibilities of configurations of masculinity and paternity. Ciampa s (1996) concept of identity and Connel s (1995) concept of masculinities were used as a support for the process of understanding. The contextualization required an explicitation of the data collection process, research concerning paternity, poor/migrant families and social policies directed at the families. Special emphasis was given to the social problem that consists in the absence of men, especially of fathers, in the social accompaniments to the families in situation of vulnerability; an absence which presents itself in spite of the fact that most of the benefited families are composed by men (IBGE/PNAD/2007). The difficulties of men in providing support and the absence of expectations that they may have a positive participation in the family be among the elements that allow them to be little considered by the social policies directed at the families in situation of vulnerability. The analysis of the history of life showed mobility in the way that the subject understands and exercises his masculinity, allowing new configurations of affective relationships and the incorporation of activities previously seen as women s responsibility. It also showed how paternity exerted by a poor father can expand itself and incorporate direct and affectionate care for the sons, as well as the exercise of citizenship